Assessment of Nurses' Knowledge towards Cardiopulmonary Resuscitation at Al-Najaf City's Teaching Hospital. - Batool Amin Jaddoue Al-Ani; Mohammed Abdu al-Kareem Mustafa (Kufa Journal for Nursing Sciences)
Objective: aimed to assess the nurses' knowledge concerning cardiopulmonary resuscitation and to find out the association between the knowledge scores of the nurses and their demographic variables of age, gender, level of education, years of experience, and training session.